Blood glucose monitoring in type 2 diabetes - Nepalese patients' opinions and experiences - Sujata Sapkota; Jo-anne E Brien; Parisa Aslani (Taylor & Francis Group, 2017)
Background: Blood glucose monitoring forms a vital component of diabetes care. Monitoring conducted at home using glucometers, and in laboratories by professionals, are two common methods of blood glucose monitoring in clinical practice. Objective: To investigate Nepalese patients' perceptions and practices of blood glucose monitoring in diabetes. Methods: In-depth interviews were conducted with 48 Nepalese participants with type 2 diabetes in Sydney and Kathmandu. The interviews were audio-recorded, transcribed verbatim and thematically analysed. Results: In Australia, most participants perceived home monitoring as useful; and both home and laboratory monitoring were conducted at fairly regular intervals. In Nepal, only a small number conducted home monitoring and the laboratory method formed the primary method of day-to-day monitoring. The laboratory method was preferred due to easy access to laboratories, lack of faith in glucometers and perceptions that home monitoring is costlier. However, overall monitoring was irregular in Nepal. In addition to the healthcare system which enabled cheaper self-monitoring in Australia, Nepalese in Australia also tended to have a better understanding about the purpose of home monitoring. Conclusions: This study has highlighted the disparity in perceptions and practices related to blood glucose monitoring. Understanding the importance of blood glucose monitoring and access to affordable resources are critical facilitators for conducting regular monitoring. Both patient and health-system factors play a key role in ensuring continued diabetes monitoring and management.